The "China Reset" for International Undergraduate Enrollment - Choudaha, Rahul (International Higher Education, 2020)
Chinese undergraduate students were an economic bonanza for American universities in times of shrinking college-age population and dwindling budgets. Recent trends indicate a stagnation and even a decline in Chinese undergraduate student enrollment at many universities. This "China reset" will pose severe challenges for universities and press them to reinvest in the diversification of their student body and supporting student success.